Factors Affecting the Awareness of Biodiversity Conservation Among Students in Malaysia Private University - Jalil, Nurul Jannah; Sharif, Zainon Mat (International Journal of Engineering and Technology, 2018)
Recently, biodiversity loss has become direr international. Human behavior is one of the causes that harm the biodiversity richness. Malaysia which is known as the megadiversity country also facing with the similar problem. Conservation of the biodiversity must be taken seriously and importantly by people to maintain the relationship between human and nature because we are affecting each other. Thus, this research was aiming to evaluate the relationship between human attitude, experience and knowledge toward the awareness of biodiversity conservation. The research was conducted using 4 variables from Ajzen’s Theory of Planned Behavior (TPB) which are behavior, perceived behavioral control, subjective norms and attitude. This study was carried out in Malaysia by conducting a survey of 30 students from a private university. The findings of this study indicate that the mentioned have given the positive effect to the awareness of biological diversity conservation. In addition, the relation of knowledge and attitude also show the great correlation between themselves. Therefore, knowledge, experience and attitude are the factors that could increase peoples' awareness towards the biodiversity conservation and knowledge is the greatest influence in creating peoples' awareness.